Forecasting of Biodiesel Prices in Thailand using Time Series Decomposition Method for Long Term from 2017 to 2036 - Laung-Iem, Kornkamol; Thanarak, Prapita (International Journal of Energy Economics and Policy, 2021)
Currently, the Thailand government is promoting biofuel, especially the producer of biodiesel. Starting from 2015, the Ministry of Energy of Thailand has determined that the palm oil remaining from domestic consumption is 14 million liters per day in 2036. Forecasting biodiesel prices are most important since biodiesel price volatility affects renewable energy consumption in the future. This paper presents the biodiesel prices in Thailand with the time series decomposition method. The source of time series data comes from the Energy Policy and Planning Office, Ministry of Energy of Thailand, monthly average retail price of regular-grade biodiesel, during 2007 – 2016, 120 months in total. This study aims to use forecasting methods to deter biodiesel prices in Thailand over the next 20 years, from 2017 to 2036. This solution starts with decomposing data into a trend, a cycle, seasonal, and any irregular components and then calculates biodiesel prices with a multiplicative model. The model shows a continuous decreasing trend of biodiesel prices from around 27.50 to 25.84 THB/liter in 2017 to 22.36 THB/liter in 2036. Moreover, the forecasting method has the least mean absolute present error (MAPE) at 0.24651. Keywords: Biodiesel, Forecasting, Time-Series Method JEL Classifications: C01, C10, E17, O21 DOI: https://doi.org/10.32479/ijeep.10666